Tissue crossmatch before corneal transplantation. Issue 1 (23rd December 2003) - Borderie, V M; Scheer, S; Bourcier, T; Touzeau, O; Laroche, L
Abstract : Aim: To investigate the influence of anticorneal antibodies on the outcome of transplantation in recipients before penetrating keratoplasty. Methods: 100 consecutive penetrating keratoplasties performed between July 1995 and June 1996 were included in this study. Donor corneoscleral rim cryosections were incubated with recipient serum. Fixation of recipient IgM on donor corneas was revealed with a polyclonal anti-human μ-chain antibody. The mean follow up time was 61 months. Five years after transplantation, 63% of patients were available for follow up. During the follow up period, 15% of keratoplasties failed because of irreversible rejection. Results: Anti-donor stromal lamellae IgM were found in 14 recipients. Anti-donor keratocyte IgM were present in 28 recipients. Dilution of recipient serum (up to 1/800) did not modify the results of positive crossmatch assays. Crossmatch assays performed with positive recipient sera and negative donor corneoscleral rims were negative. No significant influence of IgM crossmatch results on graft survival and rejection-free graft survival was found. Conclusion: Donor specific anticorneal stroma IgM were found in 28% of recipients before transplantation. This pre-immunisation was not associated with a higher risk of transplantation rejection.